2011
DOI: 10.1074/jbc.m111.264374
|View full text |Cite
|
Sign up to set email alerts
|

Multiligand Specificity of Pathogen-associated Molecular Pattern-binding Site in Peptidoglycan Recognition Protein

Abstract: The peptidoglycan recognition protein PGRP-S is an innate immunity molecule that specifically interacts with microbial peptidoglycans and other pathogen-associated molecular patterns. We report here two structures of the unique tetrameric camel PGRP-S (CPGRP-S) complexed with (i) muramyl dipeptide (MDP) at 2.5 Å resolution and (ii) GlcNAc and ␤-maltose at 1.7Å resolution. The binding studies carried out using surface plasmon resonance indicated that CPGRP-S binds to MDP with a dissociation constant of 10 ؊7 M,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(20 reference statements)
0
12
0
1
Order By: Relevance
“…The excellent fittings of both glycan moieties in the subsite with extensive intermolecular contacts indicated that this subsite is formed optimally for interacting with glycan moieties. The previously determined structures of the complexes of CPGRP-S with other glycan moiety-containing PAMPs such as LPS (4), LTA (4), and muramyl dipeptide (5) showed that their glycan moieties also occupied the same pocket as observed in the present structures, whereas other aliphatic attachments of these molecules were adjusted into other parts of the cleft (Fig. 7).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The excellent fittings of both glycan moieties in the subsite with extensive intermolecular contacts indicated that this subsite is formed optimally for interacting with glycan moieties. The previously determined structures of the complexes of CPGRP-S with other glycan moiety-containing PAMPs such as LPS (4), LTA (4), and muramyl dipeptide (5) showed that their glycan moieties also occupied the same pocket as observed in the present structures, whereas other aliphatic attachments of these molecules were adjusted into other parts of the cleft (Fig. 7).…”
Section: Discussionmentioning
confidence: 73%
“…These steps further reduced the values of R cryst factors to 25.3 and 27.8% for structures GlcNAc and MurNAc, respectively. The Fourier (2 F o Ϫ F c ) and difference Fourier (F o Ϫ F c ) maps computed at this stage showed the presence of significant non-protein electron densities at the ligand binding cleft in molecule C. It may be recalled that the ligand binding site in CPGRP-S is located in molecule C at the C-D contact (4,5). The ligands GlcNAc and MurNAc were fitted well into the electron densities (Fig.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…176-180 Several studies elucidate specific interactions between human PGRPs and peptidoglycan using synthetic peptidoglycan monomers. 178,181-183 …”
Section: Muropeptides In Eukaryotic Immune Recognition Of Bacteriamentioning
confidence: 99%
“…That is an extensive contribution. (Salunke et al, 1985;Banerjee et al, 1994Banerjee et al, , 1996Sankaranarayanan et al, 1996;Singh et al, 2001;Sharma et al, 2011;Rastogi et al, 2014) We need to include many areas like non-aqueous enzymology, enzyme promiscuity and moonlighting proteins in our syllabi and encourage people to work in these areas. The first one offers an opportunity for biocatalyst-based synthesis of industrial and drug intermediates, agrochemicals and biosurfactants (Gupta, 1992;Halling, 1994;Carrea and Riva, 2000;Hudson et al, 2005).…”
Section: Applied Bio-catalysis and "Make In India" Programmentioning
confidence: 99%